A holistic study to understand the detoxification of mycotoxins in maize and impact on its molecular integrity using cold atmospheric plasma treatment. (15th December 2019) - Wielogorska, Ewa; Ahmed, Yusuf; Meneely, Julie; Graham, William G.; Elliott, Christopher T.; Gilmore, Brendan F.
Highlights: CAPP efficiency was shown to vary significantly depending on analytes' structure. Over 60% removal of AFB1 and FB1 in maize was demonstrated within 10 min of treatment. No hepatotoxicity in vitro in treated maize samples was observed. Significant differences were detected in matrix constituents of the treated maize. Abstract: The need for safe and quality food, free from the presence of hazardous contaminants such as mycotoxins is an on-going and complex challenge. Cold atmospheric pressure plasma (CAPP) has the potential to contribute to achieving this goal. Decontamination efficacy of CAPP against six of the most common mycotoxins found in foods and feedstuffs was assessed herein. Concentration reduction of up to 66% was achieved in maize for both aflatoxin B1 and fumonisin B1 . Degradation products were detected only in the case of aflatoxin B1 and zearalenone and were tested on human hepatocarcinoma cells with no increase in cytotoxicity observed. Analysis of treated maize revealed substantial changes to small molecular mass components of the matrix. While CAPP shows promise in terms of mycotoxin detoxification important questions concerning potential changes to the nutritional and safety status of the food matrix require further investigations.